2001
DOI: 10.1002/0471142301.ns0814s17
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Vocalizations in Rat and Mouse Pups

Abstract: The ultrasonic vocalization (USV), or isolation calling response, of infant rats and mice has been studied as a measure of the intensity of an aversive affective state and as an early communicative behavior between pup and mother. The four protocols described in this unit are for the basic isolation testing procedure, and for elicitation of the contact quieting response to littermates and/or dam, the potentiation of isolation calling response by a prior brief maternal interaction and the predator-induced suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 32 publications
5
116
0
Order By: Relevance
“…The reduction of isolation-induced USVs at P17 also constituted an anxiolytic effect of PS (Morgan et al, 1999;Hofer et al, 2002), consistent with a previous study that found PS suppresses USVs at P14 (Morgan et al, 1999). The pitch of USVs from control pups decreased with age, as previously reported (Kromkhun et al, 2013), but increased with age in PS pups, further suggesting atypical development following PS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The reduction of isolation-induced USVs at P17 also constituted an anxiolytic effect of PS (Morgan et al, 1999;Hofer et al, 2002), consistent with a previous study that found PS suppresses USVs at P14 (Morgan et al, 1999). The pitch of USVs from control pups decreased with age, as previously reported (Kromkhun et al, 2013), but increased with age in PS pups, further suggesting atypical development following PS.…”
Section: Discussionsupporting
confidence: 91%
“…The pitch of USVs from control pups decreased with age, as previously reported (Kromkhun et al, 2013), but increased with age in PS pups, further suggesting atypical development following PS. Isolation-induced USVs are inherently social (Hofer et al, 2002;Harmon et al, 2008), and reductions of USVs have been found in rodent models of ASDs (Crawley, 2007;Higashida et al, 2011). Diminished USVs in rat pups are suggested to model the lack of crying observed in some children with ASDs (Crawley, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucial to the diagnosis of autism are impairments in communication, including delays in verbal language and stereotyped, repetitive language patterns (1). Hidden from normal human detection, mouse communicative strategies include numerous olfactory cues as well as ultrasonic vocalizations (USVs) (8,9). Mice begin vocalizing shortly after birth, peak in vocalization rates around postnatal day 8 (P8), and continue vocalizing, albeit at reduced rates, throughout adulthood (10).…”
mentioning
confidence: 99%
“…Both adult and infant USVs are decreased by anxiolytic drugs and increased by anxiogenic drugs (Gardner 1985;Insel et al 1986;Cuomo et al 1988;Branchi et al 2001;Jelen et al 2003), suggesting that they reflect an aversive emotional state of the animal, although the pharmacology supporting infant and adult USV appears to diverge (Simola 2015). Moreover, at least in older pups with a functional amygdala (.PN10), the presence of an imminent threat, such as predator odor presentation, inhibits USV emission (Takahashi 1992;Shair et al 1998;Hofer et al 2001;Wiedenmayer and Barr 2001;Moriceau et al 2004;Wiedenmayer et al 2005). Therefore, USV are increased at all ages as the level of anxiety increases (e.g., sustained fear) and inhibited by phasic fear, reflecting a differential USV modulation by anxiety and fear (Jelen et al 2003).…”
mentioning
confidence: 99%